2019
DOI: 10.3390/insects10020045
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Selected Synthetic Insecticides and Botanicals against Fall Armyworm, Spodoptera frugiperda, in Maize

Abstract: Fall armyworm (FAW) was reported for the first time in Africa in 2016. FAW is widely distributed in Ethiopia, causing significant damage to maize. Nine synthetic insecticides belonging to different chemical groups and 11 pesticidal plants (botanicals) were tested for their efficacy against FAW under laboratory, greenhouse, and field conditions. In the laboratory, Radiant, Tracer, Karate, and Ampligo caused over 90% larval mortality 72 h after application. Malathion had moderate activity, causing 51.7% mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
165
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(219 citation statements)
references
References 19 publications
12
165
1
3
Order By: Relevance
“…Very few studies have reported on insecticide control efficacy since the spread. One study in Ethiopia reported close to baseline susceptibility towards diamides and several other insecticide classes (Sisay et al 2019). If true, this is extremely fortunate, and is probably accounted for by an extreme genetic bottleneck in the founders of the Afro-Asian population, in which insufficient genetic diversity was present for resistance to emerge (Day et al 2017).…”
Section: Tablementioning
confidence: 96%
“…Very few studies have reported on insecticide control efficacy since the spread. One study in Ethiopia reported close to baseline susceptibility towards diamides and several other insecticide classes (Sisay et al 2019). If true, this is extremely fortunate, and is probably accounted for by an extreme genetic bottleneck in the founders of the Afro-Asian population, in which insufficient genetic diversity was present for resistance to emerge (Day et al 2017).…”
Section: Tablementioning
confidence: 96%
“…A high mortality of FAW was reported with extracts of Jatropha curcas, Militia ferruginea, Phytolacca dodecandra, Scinus molle, Melia abyssinica, Nicotiana tabacum, Lantana camara, Chenopodium ambroides, Azadirachta indica and Jatropha gossypifolia [26]. This is the first report where these plant species were evaluated against FAW in Africa-Ethiopia.…”
Section: Plant Species Action Refsmentioning
confidence: 90%
“…Mortality, decreased pupal weight [26,27] Anacardiaceae Schinus molle L. High mortality [26] Annonaceae Annona squamosa L. Decreased pupa weight, increased larval mortality [33] Apiaceae Zingiberaceae Zingiber officinale L. Mortality [36] The essential oil of Cymbopogon flexuosus was reported to be lethal to FAW (LC 50 = 1.35 mg Ll −1 ) when supplemented in to an artificial diet at 2.25, 2.5 and 4 mg Ll −1 concentrations and 18.85 h median lethal time (LT 50 ). The insecticidal activity of citral was not significantly different to the essential oil, suggesting that citral, a compound of this essential oil caused insecticidal effects of the Cymbopogon flexuosus essential oil to FAW [80].…”
Section: Plant Species Action Refsmentioning
confidence: 99%
See 2 more Smart Citations